Qadzaf Dalam Perspektif Fikih Jinayah : Pengertian, Unsur-Unsur Dan Hukuman Bagi Pelaku - Nur, Nur Rahmawati; Mad Sa’i (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Qadzaf is one of the acts that is strictly prohibited in Islam because it is related to accusations of adultery without valid evidence. In Islamic jurisprudence, qadzaf is seen as a serious criminal act that can damage a person's honor and dignity. Islam highly protects human honor and strictly prohibits the act of accusing without a basis in truth, because this kind of accusation can have negative impacts, such as slander, division, and social damage. The method used in this study is a descriptive-analytical library research. Data collection was carried out through document analysis, by reviewing books and journal articles that are relevant to the topic discussed. The results of this study indicate that qadzaf linguistically also means accusing, throwing stones or other objects, while terminologically, qadzaf means accusing of adultery. So qadzaf is accusing a muhsan (adult, sane, free, Muslim, and good person) of committing adultery. Then the elements of qadzaf are three, namely the accusation of adultery or eliminating lineage, the accused person is a muhshan person and there is evil intent and unlawful intention. In addition to the elements of qadzaf in qadzaf there is a punishment for the perpetrator, namely the main punishment (volume or lashing eighty times) and additional punishment (not accepting his testimony).